2021
DOI: 10.1108/aaaj-03-2020-4466
|View full text |Cite
|
Sign up to set email alerts
|

Into the woods of corporate fairytales and environmental reporting

Abstract: PurposeUsing a dialogic approach to narrative analysis through the lens of fairytale, this paper explores the shared construction of corporate environmental stories. The analysis provided aims to reveal the narrative messaging which is implicit in corporate reporting, to contrast corporate and stakeholder narratives and to bring attention to the ubiquity of storytelling in corporate communications.Design/methodology/approachThis paper examines a series of events in which a single case company plays the central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 62 publications
0
21
0
4
Order By: Relevance
“…O tema, ao ser debatido pelos autores, destaca principalmente as dimensões ambiental e social da sustentabilidade. Ainda assim, não é possível descartar que há também influência da dimensão econômica (Morrison & Lowe, 2021).…”
Section: Etapa 5: Análise Em Nível Do Estudounclassified
See 2 more Smart Citations
“…O tema, ao ser debatido pelos autores, destaca principalmente as dimensões ambiental e social da sustentabilidade. Ainda assim, não é possível descartar que há também influência da dimensão econômica (Morrison & Lowe, 2021).…”
Section: Etapa 5: Análise Em Nível Do Estudounclassified
“…No que se refere a construção de sentido a partir de uma perspectiva individual sobre a sustentabilidade nas organizações, atribui-se destaque àqueles que são responsáveis pelas discussões acerca do tema, aos indivíduos que assumem a liderança das áreas de responsabilidade social corporativa, por exemplo (Gond, Cabantous & Krikorian, 2018), e que, de maneira geral, orientam-se pelo interesse de mitigar, ou anular os efeitos negativos das ações organizacionais (Matejek & Gössling, 2014;Morrison & Lowe, 2021;Rossoni et al, 2020;Zanoni et al, 2021). Estes o fazem pautando-se nos valores estabelecidos pela estrutura e cultura da estrutura em que estão, mas também o fazem pautando-se em seus valores, crenças e conhecimento (Dieleman & Koning, 2020).…”
Section: Etapa 5: Análise Em Nível Do Estudounclassified
See 1 more Smart Citation
“…Accounting literature has drawn attention to another sort of plurality: that of stakeholders' voices. Examples are dialogic/polylogic (Brown, 2009;Brown and Dillard, 2015;Kingston et al, 2020;Morrison and Lowe, 2021), heteroglossic (Dillard and Roslender, 2011) or agonistic pluralism (Brown and Dillard, 2013). These stand in opposition to univocal accounts that assume a single truth or a single viewpointusually that of financial markets.…”
Section: Stakeholders' Voices and Values In Valuationmentioning
confidence: 99%
“…In practice, polyvocal accounts take the form of a kind of parallel plurality through shadow or counter-accounts (e.g. Laine and Vinnari, 2017; Morrison and Lowe, 2021). Scholars have suggested that it may be possible for accounting devices, reports, accounts, etc., to be polyvocal, however the few empirical studies that have examined the production of such accounts have found that a polyvocal account does not emerge easily from stakeholder engagement (e.g.…”
Section: Relevant Literaturementioning
confidence: 99%